Capacitor

The introduction of an intermediate layer with a conductive component concentration gradient addresses thermal stress issues, enhancing the reliability and capacitance of capacitors under high temperature conditions.

JP7663572B2Active Publication Date: 2025-04-16KYOCERA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022524376
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-19
Filing Date
2021-05-07
Publication Date
2025-04-16
Estimated Expiration
2041-05-07

AI Technical Summary

Technical Problem

Existing capacitors face challenges in achieving high capacitance and reliability under high temperature conditions due to thermal stress between dielectric and internal electrode layers.

Method used

Incorporating an intermediate layer with a concentration gradient of conductive components between dielectric and internal electrode layers, where the conductive component concentration decreases from the internal electrode layer to the dielectric layer, alleviating thermal stress and improving reliability.

Benefits of technology

The intermediate layer with a concentration gradient enhances the capacitor's resistance to thermal shock and improves reliability under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663572000002
    Figure 0007663572000002
  • Figure 0007663572000003
    Figure 0007663572000003
  • Figure 0007663572000004
    Figure 0007663572000004
Patent Text Reader

Abstract

A capacitor according to the present invention comprises a laminate and an external electrode positioned on the surface thereof. The laminate has dielectric layers and internal electrode layers. A plurality of the dielectric layers and internal electrode layers are laminated in an alternating manner. The laminate further has an intermediate layer that is positioned between a dielectric layer and an internal electrode layer and that contains dielectric components of the dielectric layer and conductive components of the internal electrode layer. The intermediate layer has a concentration gradient in which the concentration of the conductive components decreases from the internal electrode layer to the dielectric layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a stacked capacitor. [Background technology]

[0002] An example of the prior art is described in Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-4027 Summary of the Invention

[0004] The capacitor of the present disclosure comprises a laminate having alternately stacked dielectric layers and internal electrode layers, and an external electrode located on a surface of the laminate and electrically connected to the internal electrode layer. The laminate further comprises an intermediate layer located between the dielectric layer and the internal electrode layer and containing a dielectric component of the dielectric layer and a conductive component of the internal electrode layer. The intermediate layer has a concentration gradient in which the concentration of the conductive component decreases from the internal electrode layer to the dielectric layer. [Brief description of the drawings]

[0005] The objects, features and advantages of the present disclosure will become more apparent from the following detailed description and drawings.

[0006] [Figure 1] FIG. 2 is an external perspective view of a capacitor. [Diagram 2] FIG. 2 is a cross-sectional view taken along the cutting line of FIG. [Diagram 3] FIG. 2 is an enlarged schematic view of a cross section of a laminate. [Figure 4A] 10 is a graph of a comparative example showing the change in nickel concentration in the intermediate layer. [Figure 4B] 1 is a graph of Example 2 showing the change in nickel concentration in the intermediate layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Capacitors having the basic configuration of the present disclosure, which are one of the electronic components mounted in electronic devices, are required to have high capacitance and are desired to have various improved characteristics.

[0008] For example, the multilayer ceramic capacitor described in Patent Document 1 has internal electrode material diffused within the ceramic body, and the diffusion distance of the internal electrode material is set to 3 to 30% of the distance between the internal electrodes, thereby reducing the temperature change of capacitance and achieving high reliability under high temperature conditions.

[0009] The capacitor of the present disclosure will be described below with reference to the drawings. Note that the capacitor of the present disclosure is not limited to the specific embodiments described below. The capacitor of the present disclosure may include various aspects as long as they are in accordance with the spirit or scope of the general concept defined by the appended claims.

[0010] FIG. 1 is an external perspective view of a capacitor. FIG. 2 is a cross-sectional view taken along the cutting line of FIG. 1. A capacitor 100 shown as an example of an embodiment of the present disclosure includes a laminate 1 and an external electrode 3 located on its surface. The laminate 1 has a dielectric layer 5 and an internal electrode layer 7, and the dielectric layers 5 and the internal electrode layers 7 are alternately laminated. The laminate 1 of this embodiment is, for example, a rectangular parallelepiped shape, and the dielectric layers 5 and the internal electrode layers 7 are both rectangular in plan view from the lamination direction. One side of the internal electrode layer 7 is exposed on a side surface of the laminate 1, and the external electrode 3 covers this side surface to electrically connect the internal electrode layer 7 and the external electrode 3. In FIG. 2, the number of layers of the dielectric layers 5 and the internal electrode layers 7 is simplified to a few layers, but the number of layers of the dielectric layers 5 and the internal electrode layers 7 may be, for example, several hundred layers.

[0011] FIG. 3 is an enlarged schematic diagram of a cross section of a dielectric layer. The dielectric layer 5 is composed of, for example, a plurality of crystal grains containing titanate. The crystal grains may be crystal grains containing a dielectric component mainly composed of titanate. Here, the main component refers to the component that is contained in the largest amount in the crystal grains. The main component of titanate refers to a state in which the content of titanate in the crystal grains is greater than that of other components. Examples of titanate include barium titanate, magnesium titanate, and lanthanum titanate. A mixture of these types of titanate may be used as the titanate. By using barium titanate with a high dielectric constant, the capacitance of the capacitor 100 can be increased.

[0012] The crystal particles containing titanate are crystal particles having an average particle size of, for example, 0.1 to 0.5 μm. The average particle size of the crystal particles is measured, for example, by the following procedure. First, the fracture surface of the sample, which is the laminate 1 after sintering, is polished. Then, the polished sample is photographed for its internal structure using a scanning electron microscope, a circle containing 50 to 100 crystal particles is drawn on the photograph, and the crystal particles within and around the circle are selected. Next, an existing image analysis program is used to extract the outline of each crystal particle contained within the region to determine the cross-sectional area. Based on the obtained cross-sectional area, the circle-equivalent diameter of each crystal particle is calculated, and the average particle size is determined from the average value.

[0013] The internal electrode layers 7 are made of conductive components such as metal materials, and may be made of, for example, nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), etc. Also, alloys containing these metal materials may be used. The external electrodes 3 may be made of the same or similar metal materials as the internal electrode layers 7.

[0014] In this embodiment, the laminate 1 further includes an intermediate layer 6 located between the dielectric layer 5 and the internal electrode layer 7, and containing the dielectric component of the dielectric layer 5 and the conductive component of the internal electrode layer 7. The intermediate layer 6 has a concentration gradient in which the concentration of the conductive component decreases from the internal electrode layer 7 to the dielectric layer 5. A layer such as the intermediate layer 6 in which the contained components have a concentration gradient is called a gradient layer. In the intermediate layer 6, the concentration of the conductive component gradually changes along the thickness direction. The conductive component concentration is highest on the internal electrode layer 7 side of the intermediate layer 6, and is lowest on the dielectric layer 5 side.

[0015] In the laminate 1, the conductive component contained in the internal electrode layer 7 penetrates into the dielectric layer 5 to form a region containing the dielectric component of the dielectric layer 5 and the conductive component of the internal electrode layer 7. Conventionally, in the region where the conductive component penetrates into the dielectric layer 5, the conductive component exists uniformly or randomly, for example. In addition, the concentration of the diffused conductive component is low. In this embodiment, as described above, the intermediate layer 6 is a gradient layer having a concentration gradient of the conductive component, and relieves the thermal stress generated between the dielectric layer 5 and the internal electrode layer 7 under high temperature conditions. This makes it possible to improve the reliability of the capacitor 100, which is resistant to thermal shock, in a high temperature environment.

[0016] The intermediate layer 6 has a thickness of 0.04 to 0.2 μm. If the thickness exceeds 0.2 μm, the conductive component content of the intermediate layer 6 increases, and the conductive component of the internal electrode layer 7 decreases accordingly, which may reduce the continuity of the internal electrode layer 7 and reduce the capacitance.

[0017] The content of the conductive component in the intermediate layer 6 is 0.005 to 0.035 mol%. This means that the content of the conductive component on the internal electrode layer 7 side of the intermediate layer 6, which has the highest conductive component concentration, is, for example, at most 0.035 mol%, and the content of the conductive component on the dielectric layer 5 side of the intermediate layer 6, which has the lowest conductive component concentration, is, for example, at least 0.005 mol%. The concentration gradient of the conductive component in the intermediate layer 6 may be within the range of 0.005 to 0.035 mol%. For example, the intermediate layer 6 may have a concentration gradient in which the content of the conductive component on the internal electrode layer 7 side is 0.015 mol% and the content of the conductive component on the dielectric layer 5 side is 0.005 mol%. Also, for example, the intermediate layer 6 may have a concentration gradient in which the content of the conductive component on the internal electrode layer 7 side is 0.02 mol% and the content of the conductive component on the dielectric layer 5 side is 0.01 mol%. Also, for example, the intermediate layer 6 may have a concentration gradient in which the content of the conductive component on the internal electrode layer 7 side is 0.035 mol %, and the content of the conductive component on the dielectric layer 5 side is 0.02 mol %.

[0018] In the following, the dielectric component of the dielectric layer 5 is assumed to be barium titanate, and the conductive component of the internal electrode layer 7 is assumed to be nickel. The intermediate layer 6 contains barium titanate and nickel, and has a concentration gradient in which the nickel concentration decreases from the internal electrode layer 7 to the dielectric layer 5. For example, it is known that nickel diffuses into barium titanate during firing, but the amount of diffusion is only small. It has been found that nickel can be present in barium titanate at a high concentration by performing heat treatment in an oxidizing atmosphere and then heat treatment (main firing) in a conventional reducing atmosphere in the firing process of the laminate 1. Although the details of the mechanism are unknown, it is speculated as follows. A part of nickel is oxidized by heat treatment in an oxidizing atmosphere to generate nickel oxide. The generated nickel oxide has a higher affinity with unsintered barium titanate than nickel and enters the barium titanate. The subsequent heat treatment in a reducing atmosphere progresses the sintering of barium titanate, and nickel oxide is reduced to nickel. In the obtained laminate 1, an intermediate layer 6 having a nickel concentration gradient is formed between the dielectric layer 5 and the internal electrode layer 7.

[0019] The thickness of the intermediate layer 6, the nickel content in the intermediate layer 6, the gradient of the concentration, etc. depend on the penetration depth and amount of nickel oxide into barium titanate, and therefore can be controlled by the atmospheric gas composition, heat treatment temperature, and heat treatment time in the heat treatment in an oxidizing atmosphere. In the heat treatment, whether the atmosphere is an oxidizing atmosphere in which nickel is oxidized or a reducing atmosphere in which nickel oxide is reduced or nickel is not oxidized can be controlled by the oxygen partial pressure of the atmospheric gas components. The oxygen partial pressure of the atmospheric gas components is determined by the partial pressures of hydrogen gas and water vapor gas in the atmospheric gas. The higher the ratio of hydrogen gas and water vapor gas in the atmospheric gas, the lower the oxygen partial pressure. Also, the higher the temperature of the atmospheric gas, the higher the oxygen partial pressure. If the oxygen partial pressure of the atmospheric gas is higher than the equilibrium oxygen partial pressure of nickel, it becomes an oxidizing atmosphere in which nickel is oxidized, and if the oxygen partial pressure of the atmospheric gas is lower than the equilibrium oxygen partial pressure of nickel, it becomes a reducing atmosphere in which nickel is reduced.

[0020] For example, when the ratio (H2 / H2O) of hydrogen gas to water vapor gas in the atmosphere gas is 1 / 2000 and the temperature is 700 to 800°C, the oxygen partial pressure of the atmosphere gas becomes higher than the equilibrium oxygen partial pressure, resulting in an oxidizing atmosphere. By heat treatment in such an oxidizing atmosphere, nickel is oxidized and penetrates into the unsintered barium titanate. Thereafter, when the ratio (H2 / H2O) of hydrogen gas to water vapor gas in the atmosphere gas is 1 / 20 and the temperature is 800°C or higher, the oxygen partial pressure of the atmosphere gas becomes lower than the equilibrium oxygen partial pressure, resulting in a reducing atmosphere. In the reducing atmosphere, sintering of barium titanate and reduction of nickel oxide proceed, and a laminate 1 including an intermediate layer 6 is obtained.

[0021] Although the conductive component is nickel in the above description, the same applies to other conductive components. The oxidizing atmosphere and reducing atmosphere of copper can be controlled by the magnitude relationship between the oxygen partial pressure of the atmospheric gas and the equilibrium oxygen partial pressure of a conductive component such as copper.

[0022] A method for manufacturing the capacitor of this embodiment will be described. First, a ceramic slurry is prepared by using a ball mill or the like with a dielectric powder together with an organic resin such as polyvinyl butyral resin and a solvent such as toluene and alcohol, and then the ceramic slurry is formed into a ceramic green sheet on a substrate by a sheet forming method such as a doctor blade method or a die coater method. The thickness of the ceramic green sheet is preferably 0.8 to 1.5 μm in order to make the dielectric layer 5 thin to increase its capacity and to maintain high insulation.

[0023] By the way, the dielectric materials used in the manufacture of multilayer ceramic capacitors are, depending on the desired dielectric properties, barium titanate (BaTiO3, hereinafter referred to as BT powder), BaTiO3 powder in which alkaline earth elements such as calcium or strontium are dissolved in the barium site, and 1-x Ca x TiO3 (x=0.01~0.1, hereafter referred to as BCT powder) powder or Ba 1-x Sr xTiO3 (x=0.01-0.1, hereafter referred to as BST powder) powder, or barium titanate in which calcium is dissolved in the barium site and zirconium is dissolved in the titanium site. 1-x Ca x Ti 1-y Zr y O3 (x=0.01 to 0.1, y=0.05 to 0.5, hereinafter referred to as BCTZ powder) powder can be used.

[0024] Among the above powders, BT powder is suitable because it can provide a multilayer ceramic capacitor with a relatively small temperature coefficient of capacitance change over a wide temperature range centered on room temperature. The BT powder preferably has a Ba / Ti molar ratio of 1.001 to 1.009 and an average particle size of 0.1 to 0.2 μm. This facilitates thinning of the dielectric layer 5, and the BT powder can provide a multilayer ceramic capacitor with excellent high-temperature load life under the firing conditions described below.

[0025] In addition, the dielectric powder used in manufacturing the multilayer ceramic capacitor of this embodiment may be a barium titanate powder to which a predetermined amount of sintering aids such as vanadium, magnesium, rare earth elements (RE), manganese, and glass powder mainly composed of SiO2 have been added. When using these, it is possible to obtain a capacitor with a high high temperature load life and a high capacitance per unit volume.

[0026] For example, V2O5 powder, MgO powder, at least one oxide powder of rare earth element (RE) selected from Y2O3 powder, Dy2O3 powder, Ho2O3 powder, and Yb2O3 powder, and a powder containing manganese (here, MnCO3 powder is used) are added to BT powder having a purity of 99.9% or more, a Ba / Ti molar ratio of 1.001 to 1.009, and an average particle size of 0.1 to 0.2 μm. In this case, the composition may be 0.03 to 0.08 mol of V2O5 powder, 0.9 to 1.1 mol of MgO powder, 0.4 to 0.6 mol of at least one oxide powder of rare earth element (RE) selected from Y2O3 powder, Dy2O3 powder, Ho2O3 powder, and Yb2O3 powder, and 0.2 to 0.3 mol of powder containing manganese, relative to 100 mol of BT powder.

[0027] Next, a glass powder mainly composed of SiO2 is added to the BT powder to which V2O5 powder, MgO powder, oxide powder of rare earth elements (RE) and powder containing manganese have been added within the above-mentioned ranges, and an organic binder and a solvent are added and mixed to prepare a ceramic slurry.

[0028] The glass powder used contains SiO2, BaO, CaO and Li2O as main components, and the composition may contain 0.15 to 0.70 mol of BaO, 0.15 to 0.70 mol of CaO, and 0.05 to 0.45 mol of Li2O when SiO2 is 1 mol.

[0029] The purity of these raw material reagents is preferably 99.5% or higher in order to reduce the inclusion of impurities in the sintered body that will become the resulting dielectric layer 5 and to obtain high dielectric properties.

[0030] Next, a rectangular internal electrode pattern is printed on the surface of the obtained ceramic green sheet. The conductor paste for the internal electrode pattern is prepared by mixing nickel (Ni) or an alloy powder of nickel (Ni) as the main metal component with ceramic powder (in this case, BT powder or the dielectric powder used in the ceramic green sheet is used) as a co-material, and adding an organic binder, a solvent, and a dispersant. In addition, in order to eliminate the step due to the internal electrode pattern on the ceramic green sheet, a ceramic pattern may be formed around the internal electrode pattern with substantially the same thickness as the internal electrode pattern. In this case, the ceramic component constituting the ceramic pattern may be the dielectric powder used in the ceramic green sheet in order to make the firing shrinkage in the simultaneous firing the same.

[0031] Next, a desired number of ceramic green sheets with internal electrode patterns are stacked, and a number of ceramic green sheets without internal electrode patterns are stacked on top and bottom so that the number of upper and lower layers is the same, to form a temporary laminate. The internal electrode patterns in the temporary laminate are shifted by half a pattern in the longitudinal direction. This lamination method allows the internal electrode patterns to be alternately exposed on the end faces of the laminate after cutting.

[0032] In addition to the method of laminating the ceramic green sheets after previously forming the internal electrode patterns on the main surfaces thereof, the multilayer ceramic capacitor of the present embodiment can also be formed by a method of first adhering the ceramic green sheets to a lower layer substrate, printing the internal electrode patterns thereon, drying the sheets, and then superimposing and temporarily adhering a ceramic green sheet on which an internal electrode pattern is not printed on the printed and dried internal electrode pattern, and successively adhering the ceramic green sheets to each other and printing the internal electrode patterns thereon.

[0033] Next, the temporary laminate is pressed under conditions of a higher temperature and pressure than the temperature and pressure during the temporary lamination to form a compact in which the ceramic green sheets and the internal electrode patterns are firmly adhered to each other. The compact is cut into a lattice shape to obtain a laminate (unfired) in which the ends of the internal electrode patterns are exposed.

[0034] Next, the unsintered laminate is sintered under predetermined sintering conditions to form the laminate 1. In some cases, the ridges of the laminate 1 may be chamfered, and barrel polishing may be performed to expose the internal electrode layers 7 exposed from the opposing end faces of the laminate 1. As for the sintering conditions, as described above, heat treatment may be performed in an oxidizing atmosphere with atmospheric gas components and temperature conditions that provide an oxygen partial pressure higher than the equilibrium oxygen partial pressure of nickel, and then sintering may be performed in a reducing atmosphere with different atmospheric gas components and temperature conditions.

[0035] Next, an external electrode paste is applied to the opposing ends of the laminate 1 and baked to form the external electrodes 3. In some cases, a plating film is formed on the surface of the external electrodes 3 to improve mountability. In this manner, the capacitor of this embodiment is obtained. EXAMPLES

[0036] A manufacturing method of the capacitor of the embodiment will be described. A barium titanate raw powder with a purity of 99.9%, an average particle size of 0.2 μm, and a Ba / Ti molar ratio of 1.005 was prepared. Diprosium was added as Dy2O3 as a rare earth element. Other additives included calcium carbonate powder (CaCO3), manganese carbonate powder (MnCO3), and glass powder (containing SiO2, BaO, CaO, and Li2O as main components). These were wet-mixed using a zirconia ball with a diameter of 5 mm, with a mixed solvent containing toluene and alcohol as the solvent.

[0037] Next, the wet-mixed powder was put into a mixed solvent of toluene and alcohol in which polyvinyl butyral resin had been dissolved, and wet-mixed using a zirconia ball with a diameter of 5 mm to prepare a ceramic slurry. A ceramic green sheet with a thickness of approximately 3 μm was then produced on a molding film using the doctor blade method.

[0038] Nickel powder was used as the metal of the metal paste for forming the internal electrode layers, ethyl cellulose was used as the resin for preparing the metal paste, and a mixture of dihydroterpineol-based solvent and butyl cellosolve was used as the solvent.

[0039] Next, a metal paste was printed on the prepared ceramic green sheet to prepare a green sheet with metal paste. Next, 400 layers of the prepared green sheets with metal paste were stacked, and ceramic green sheets were stacked on the upper and lower sides as cover layers to prepare a molded body. After this, the molded body was cut to prepare an unfired laminate.

[0040] The firing process was carried out under the following conditions. In firing, heat treatment was performed in an oxidizing atmosphere, and then main firing was performed in a reducing atmosphere. Here, by changing the oxidizing atmosphere, Examples 1 to 4 with different concentration gradients of the intermediate layer were obtained. Specifically, the heat treatment time in the oxidizing atmosphere was set to 20 minutes, and the temperature conditions and component ratios (ratio of hydrogen gas to water vapor gas (H2 / H2O)) were changed as shown in Table 1. In the main firing in the reducing atmosphere, the conditions were common to Examples 1 to 4. Specifically, the temperature conditions were set to a maximum temperature of 1200°C and held for 30 minutes, and the ratio of hydrogen gas to water vapor gas (H2 / H2O) was set to 1 / 10. The size of the obtained laminate was 2.0 mm x 1.25 mm x 1.25 mm.

[0041] After the obtained laminate 1 was barrel polished, external electrode paste was applied to both ends of the laminate 1 and baked at a temperature of 800°C to form external electrodes. The external electrode paste used contained Cu powder and glass. Then, an electrolytic barrel machine was used to form Ni plating and Sn plating in that order on the surface of the external electrodes to obtain a capacitor. The design value of the capacitance of the produced capacitor was set to 10.0 μF.

[0042] Comparative examples were produced by the same manufacturing method as the respective examples, except for the firing step, in which the comparative examples were fired only in a reducing atmosphere without heat treatment in an oxidizing atmosphere.

[0043] The thermal shock resistance was evaluated by a solder resistance test. In the solder resistance test, the capacitors of Examples 1 to 4 and the Comparative Example (100 pieces each) were immersed in a solder bath maintained at 305°C for 5 seconds, and after removal, the number of pieces that had cracks was counted. The results are shown in Table 1 as the number of pieces that had cracks / the number of pieces immersed.

[0044] For the intermediate layer, the thickness of the intermediate layer, the concentration on the internal electrode layer side (maximum concentration), and the concentration on the dielectric layer side (minimum concentration) were measured. The measurement method was as follows. The internal electrode layers of Examples 1 to 4 were peeled off to prepare stripped samples in which the intermediate layer was exposed. The internal electrode layers were peeled off by electrochemical nickel dissolution treatment so that the internal electrode layer would not remain on the surface of the intermediate layer. Nickel was quantified in the depth direction from the surface of the intermediate layer of the peeled sample by secondary ion mass spectrometry (SIMS). The measurement conditions for SIMS are shown below. The nickel concentration of the dielectric layer of the comparative example was also measured by SIMS in the same or similar manner. The measurement results are shown in Table 1. Analysis method: Time-of-flight secondary ion mass spectrometry (ToF-SIMS) Analytical equipment: ULVAC-PHI PHI nano ToF II Primary ion: Bi cluster ion Measurement area: 100μm square Depth direction sputtering: Ar ions 4 keV

[0045] [Table 1]

[0046] As can be seen from the results shown in Table 1, in the solder resistance test, the number of cracks generated was significantly reduced in Examples 1 to 4 compared to the Comparative Example, and excellent thermal shock resistance was obtained. Furthermore, the intermediate layer thickness, maximum concentration, and minimum concentration all changed in Examples 1 to 4, and it was found that the intermediate layer can be controlled by the conditions of the oxidizing atmosphere. In the Comparative Example, the nickel concentration in the dielectric layer 5 was lower than the minimum concentration in the Examples, and no concentration change was observed in the thickness direction of the dielectric layer.

[0047] Examples of measurement results by SIMS are shown in Figures 4A and 4B. Figure 4A shows the measurement results of the comparative example, and Figure 4B shows the measurement results of Example 2. In the graph of Figure 4, the vertical axis indicates the amount of nickel (mol%), and the horizontal axis indicates the depth (nm) from the sample surface. In the comparative example, the amount of nickel was constant at 0.003 mol%, regardless of the depth. In Example 2, the amount of nickel decreased with increasing depth, and it was confirmed that an intermediate layer with a concentration gradient was formed.

[0048] The present disclosure may have the following embodiments.

[0049] The capacitor of the present disclosure comprises a laminate having alternately stacked dielectric layers and internal electrode layers, and an external electrode located on a surface of the laminate and electrically connected to the internal electrode layer. The laminate further comprises an intermediate layer located between the dielectric layer and the internal electrode layer and containing a dielectric component of the dielectric layer and a conductive component of the internal electrode layer. The intermediate layer has a concentration gradient in which the concentration of the conductive component decreases from the internal electrode layer to the dielectric layer.

[0050] According to the capacitor of the present disclosure, the reliability of the capacitor can be improved under high temperature conditions.

[0051] Although the embodiments of the present disclosure have been described in detail above, the present disclosure is not limited to the above-mentioned embodiments, and various modifications and improvements are possible within the scope of the gist of the present disclosure. It goes without saying that all or part of the components of each of the above-mentioned embodiments can be appropriately combined within the scope of not contradicting each other. [Explanation of symbols]

[0052] 1. Laminate 3 External electrode 5 Dielectric Layer 6. Middle Tier 7 Internal electrode layer 100 Capacitor

Claims

1. a laminate having dielectric layers and internal electrode layers stacked alternately; an external electrode located on a surface of the laminate and electrically connected to the internal electrode layer, The laminate further includes an intermediate layer located between the dielectric layer and the internal electrode layer and including a dielectric component of the dielectric layer and a conductive component of the internal electrode layer, the intermediate layer has a concentration gradient in which the concentration of the conductive component decreases from the internal electrode layer to the dielectric layer, A capacitor, wherein the dielectric component comprises barium titanate and the conductive component comprises nickel.

2. The capacitor of claim 1, wherein the intermediate layer has a thickness of 0.04 to 0.2 μm.

3. 3. The capacitor according to claim 1, wherein the content of the conductive component in the intermediate layer is 0.005 to 0.035 mol %.

Citation Information

Patent Citations

  • Lamination ceramic electronic component and its manufacturing method

    JP1997102436A

  • Multilayer electronic component

    JP1998004027A

  • Manufacture of electronic component

    JP2001035741A

  • Laminated ceramic capacitor, and method of manufacturing same

    JP2007173714A

  • Laminate semiconductor ceramic capacitor having varistor functionality and method for producing same

    WO2012105437A1